Program Peningkatan Kualitas Baca Tulis Al – Qur’an Anak Usia Dini Di TPQ Sabilil Huda - Devi Rohmatus Sa’adah; Rohmad Muzakki (LP3M IAIFA Kediri, 2020)
The Qur'an education and teaching institution is an islamic educational and teaching institution outside the school or can also be referred to as non-formal education for children and aims to educate santri and santriwati (children) in order to be able to read the Qur'an properly and correctly in accordance with tajwid science as the main target. In this report entitled